Business networks in East Asian capitalisms : enduring trends, emerging patterns - Nolar, Jane; Warner, Malcom; Rowley, Chris ([London] : Elsevier : Chandos Publishing, 2016)
Annotation Business Networks in East Asian Capitalisms: Enduring Trends, Emerging Patterns builds on the foundational studies conducted in the 1990s by gathering contemporary empirical and theoretical chapters which explore these themes in a comparative perspective.The book includes contributions from authors working on the relationship between personal and business networks in countries including China, Singapore, Malaysia, Taiwan, Japan, South Korea, Vietnam, Laos, Cambodia, and Thailand.Authors emphasize enduring trends in social and business networks and/or track new emerging patterns, both within East Asian nations or between East Asia and other regions such as Europe, Africa, and the Americas.Provides contemporary, up-to-date empirical material and theoretical interpretation, charting the influence of more recent globalizing trends and institutional change in the regionIncludes studies of networks within PRC, between PRC and other regions, and in Chinese communitiesOffers studies centered on Korean, Japanese, and South East Asian NetworksIncludes a geographical scope that will be broader than other books, aiming to include studies of newly developing economies in South East Asia that share a common cultural heritage (e.g Vietnam).
5.6 Conceptualisation of Guanxi5.7 Differential Mode of Association (Chaxugeju); 5.8 The Future Role of Guanxi in Business; 5.9 Central Managed Capitalism; 5.10 Network of Guanxi Circles; 5.11 Conceptual Framework: Guanxi Capitalism Structure; 5.12 Conclusion; Appendix; References; Chapter 6: The Networking Strategies of the Jebsens and Chinese Merchants in the Late 19th and the Early 20th Centuries; 6.1 Introduction; 6.2 Formal and Informal Networks: Mechanisms and Limits; 6.3 Informal Networks: The Jebsens; 6.4 Institutionalising Semiformal Associations of Chinese Merchants; 6.5 Conclusion.
Includes bibliographical references and index.
Keywords: Business networks -- East Asia; Capitalism -- East Asia